Sexually Dimorphic Effects of Aromatase on Neurobehavioral Responses - Shay, Dusti A.; Vieira-Potter, Victoria J.; Rosenfeld, Cheryl S. (Frontiers in Molecular Neuroscience, 2018)
Aromatase is the enzyme responsible for converting testosterone to estradiol across vertebrate species. In mammals, aromatase is expressed in the testes, ovaries, brain, and other tissues. While estrogen is traditionally associated with reproduction and sexual behavior in females, our current understanding broadens this perspective to include such biological functions as metabolism and cognition in both sexes. Thus, ongoing investigations seek to highlight potentially vital sex differences in the role of aromatase, particularly regarding its centrally-mediated effects. It is now well-recognized that aromatase plays a vital and lifetime role in brain development and neurobehavioral function in both sexes. To characterize the role of systemic and brain-specific aromatase in mediating such functions, aromatase inhibitor treatments in intact and gonadectomized rodent models and aromatase knockout (ArKO) mice that systemically lack the enzyme have been employed. Humans possessing mutations within the gene encoding aromatase, CYP19, have provided useful insight into how aromatase affects brain function in a possible sex-dependent manner. A better understanding of how aromatase inhibitors, used to treat breast cancer and other clinical conditions, potentially affect neurobehavioral responses may aide in development of future therapies to combat these pernicious effects. In this review, we will discuss current knowledge of sex differences in aromatase regulation of various neurobehavioral functions in rodent models and humans. Critical gaps in our current understanding of the sexually dimorphic role of aromatase on neurobehavioral responses will be discussed, as will important future research directions.